3D analysis of Rayleigh-type surface wave in fractured media: Insights into anisotropic characteristics. (27th October 2022) - Wang, Ding; Tang, Jing
Highlights: 3D Rayleigh waves responses for fractured media are obtained using the SG-FDM. The anisotropic characteristics of Rayleigh waves of fractured media are presented. The effects of fracture scale and location on Rayleigh waves are studied. Abstract: The propagation characteristics of Rayleigh waves on the surfaces of fracture-containing media have considerable theoretical and practical significance. Limitations are associated with using two-dimensional (2D) observations of Rayleigh waves to predict fracture features, because real fractures have a complex distribution inside media. Therefore, the three-dimensional (3D) propagation of Rayleigh waves in media with directional fractures is simulated in this study by combining the staggered-grid finite difference method with parallel computing. The wave velocity and amplitude of Rayleigh waves depend on the relative direction between fracture and wave path on the medium surface. That is, Rayleigh waves exhibit clearly anisotropic characteristics for a medium with directionally distributed fractures, where the degree of anisotropy is closely related to fracture parameters, such as the fracture density and fracture scale. Two new anisotropy parameters for Rayleigh waves are defined in this study: the anisotropy of the wave velocity and the anisotropy of attenuation (transmission coefficient). For a single fracture, the minor axis of the anisotropic quasi-semiellipse and the locations of discontinuities can indicate the normal direction of the fracture and the fracture distribution range, respectively. For multiple fractures, the major axis of the anisotropic quasi-semiellipse of the Rayleigh wave has almost the same direction as the main distribution of the fracture zone. This study provides theoretical support for the accurate prediction of complex fracture parameters inside media.